Autonomous Vehicle Control System as a Mobile Robot by Artificial Neural Network - Nazmul Haque; Md Hasnat Riaz (Institute of Advanced Engineering and Science, 2017)
In this paper we have presented the artificial neural network controlled car in mobile robotics and intelligent car systems. The motion control architecture of the robot is presented with an importance on the support and directing units. This uses neural network methods and the values fundamental its design is drawn. A robust neural control system using a model of the process is also developed.